Greywater treatment technologies for aquaculture safety: Review - Sigit Kurniawan, Sigit Kurniawan; Novarini, Novarini; Erna Yuliwati, Erna Yuliwati; Eko Ariyanto, Eko Ariyanto; Marlia Morsin, Marlia Morsin; Rahmat Sanudin, Rahmat Sanudin; Suratun Nafisah, Suratun Nafisah (Elsevier, 2024)
This review intends to discuss on greywater treatment technologies, which are the physiochemical, biological and advanced oxidation process (AOP) treatment technologies that are used to remove organic, nutrient and surfactant pollutants in greywater. The focus of this study is to compare the treatment technologies to remove greywater pollutants in the coastal area. Each technology will be compared in terms of its advantages and disadvantages, including its potential in greywater treatment technologies development. Measurement parameters of water quality from other studies include physicochemical, organic content, nutrient, and surfactant that are developed from each greywater treatment mode. AOP has a huge potential in greywater treatment since the technology has a low cost of development, easy to install, and is able to be deployed on a small scale. The AOP could be combined with other treatment techniques to produce an improved output.